พฤติกรรมของประชาชนในอำเภอเมืองลำพูนในการจัดการขยะ - ปฐมพงศ์ หอมวิเชียร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study on behavior of people in Mueang Lamphun district towards waste management aimed to explore behavior of people in the studied area towards waste management. In order to collect data, questionnaires were distributed, according to the convenient sampling method, to400 people residing in Mueang Lamphun district. Then, data obtained were analyzed by the application of descriptive statistics, consisting of frequency, percentage and means. Hereafter were shown summary of the findings. The results presented that most respondents were male in the age of 20-30 years old with Bachelor’s degree. They were students with an income of 5,001-10,000 Baht. They or their family member owned the house where they lived and the house was found as a detached house with 2-3 members. They had perceived knowledge on waste and its management before and sources of information introducing this knowledge to them were television programs, school, educational institutes and government units. The findings on level of behavior towards waste management revealed that in an overall view, all 3 behavioral aspects: reuse, waste reduction, and waste sorting were ranked respectively at the moderate level. In an aspect of reuse, the top three behavioral sub-aspects were 1) collecting used-plastic bags nicely in order to reuse them later, 2) reusing the packages like plastic and glass bottles, and 3) collecting junk cloths, stuff and utensils and donating them for other’s benefits or to charity organizations. In an aspect of waste reduction, the top three behavioral sub-aspects were 1) purchasing refilled products, 2) purchasing products and services from shops promoting policy on and going along with waste reduction campaign, and 3) coordinating with community and municipality to reduce the waste. In an aspect of waste sorting, the top three behavioral sub-aspects were 1) having waste sorted by all family members before throwing, 2) throwing wastes into the right types of garbage containers, and 3) separating hazardous wastes to clearly indicate dustmen to beware of them. The findings on level of opinions towards waste management presented that in an overall view, people in Mueang Lamphun district ranked their opinions towards waste management at high level. Their top three opinions were respectively listed as follows. 1) Waste sorting made waste collecting simply and strengthened household and community’s sanitations. 2) Selling recycle wastes was not a shameful practice. 3) Waste management was considered as the base to establish discipline on environment preservation among people and youth in the community and environmental problems could be solved out by applying 3 R methods: Reuse, Reduce, and Recycle.